2007
DOI: 10.1038/mt.sj.6300145
|View full text |Cite
|
Sign up to set email alerts
|

Stem and Progenitor Cells in Skeletal Muscle Development, Maintenance, and Therapy

Abstract: Satellite cells are dormant progenitors located at the periphery of skeletal myofibers that can be triggered to proliferate for both self-renewal and differentiation into myogenic cells. In addition to anatomic location, satellite cells are typified by markers such as M-cadherin, Pax7, Myf5, and neural cell adhesion molecule-1. The Pax3 and Pax7 transcription factors play essential roles in the early specification, migration, and myogenic differentiation of satellite cells. In addition to muscle-committed sate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
464
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 509 publications
(476 citation statements)
references
References 136 publications
8
464
1
3
Order By: Relevance
“…(80) Muscle progenitor cells have been characterized as expressing the transcription factor Pax7 and are positive for the cluster differentiation markers CD34, CD44, CD56, and CD146. (45) The high expression of different mesodermal and myogenic markers in the SB-OG cell population also was observed when skeletal myocytes were isolated from different tissues of the body. (45) Therefore, this study confirms the presence of an early mesoderm stem cell population that has a multipotential differentiation ability.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…(80) Muscle progenitor cells have been characterized as expressing the transcription factor Pax7 and are positive for the cluster differentiation markers CD34, CD44, CD56, and CD146. (45) The high expression of different mesodermal and myogenic markers in the SB-OG cell population also was observed when skeletal myocytes were isolated from different tissues of the body. (45) Therefore, this study confirms the presence of an early mesoderm stem cell population that has a multipotential differentiation ability.…”
Section: Discussionmentioning
confidence: 91%
“…2C, D). Furthermore, NCAM þ cells were found to stain positive for the myogenic markers desmin þ (80% to 90%), ASMA þ (30% to 40%), and SERCA1 þ (SR-1, 19% AE 3%) (45) (Fig. 2D) and were negative for paired box transcription factor 7 positive (Pax7 þ , 25% AE 4%) (46) (Fig.…”
Section: Enrichment Of Muscle Progenitor Cells (Mpcs)mentioning
confidence: 99%
“…Nevertheless, in the last ten years, evidence has accumulated that other progenitors can contribute to skeletal muscle regeneration either by direct fusion or by entering the satellite cell pool [6][7][8][27][28][29][30][31][32][33][34][35][36] . When identified, the anatomical niche of these cells has been often associated with blood vessels (endothelial cells, pericytes and also haematopoietic cells).…”
Section: Discussionmentioning
confidence: 99%
“…The study by Mu and Li (2010) showed that incubation of primary myoblasts or C2C12 immortalised myoblasts with a transient and small concentration of TGF-β can lead to the expression of more primitive markers, Pax7 and Sca-1 [52]. However, in the aforementioned study the authors identify the expression of Pax7 and Sca-1 as an indication of reversion to an MSC phenotype, although Pax7 is more commonly used as an indicator of satellite cell phenotype, and Sca-1 has also been identified as a marker of muscle cell progenitors [54]. Therefore, it may be more likely that the presence of inflammatory factors such as TGF-β could lead to a reversion of myoblasts to an earlier muscle progenitor/satellite cell type, which may possess an osteochondrogenic potential.…”
Section: Myoblastsmentioning
confidence: 97%